2015
DOI: 10.1177/1687814015586934
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on noise radiation characteristics of pulse detonation engine–driven ejector

Abstract: The noise radiation characteristics of multi-cycle pulse detonation engine with and without ejector were investigated under different operating frequencies utilizing gasoline as fuel and air as oxidizer. The straight cylindrical ejector with convergent inlet geometry was coaxially installed at different axial locations relative to the exit of the detonation tube. In all the experiments, the equivalence ratios of gasoline-air mixture and the fill fraction were 1.2 and 1.0, respectively. The experimental results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Huang and Bavolar have also found that the combination of different environmental factors reduces performance. In other words, if their combined effects are more than those of their individual effect, they can intensify each other’s effects and have a similar effect mechanism; however, if the combined effects of environmental risk factors are equal to those of their individual effect, they will most likely have a separate effect 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Huang and Bavolar have also found that the combination of different environmental factors reduces performance. In other words, if their combined effects are more than those of their individual effect, they can intensify each other’s effects and have a similar effect mechanism; however, if the combined effects of environmental risk factors are equal to those of their individual effect, they will most likely have a separate effect 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Korobov and Golovastov [58] studied the ejector influence effectiveness of a detonation engine and their results showed that the use of an ejector can yield thrust augmentation by 17%. Huang et al [59] experimentally studied the noise radiation characteristics of multicycle pulse detonation engine with and without ejectors.…”
Section: Reviews On Experimental Analysismentioning
confidence: 99%
“…The straight cylindrical ejector had a global reduction on overall SPL at all directivity angles, and the maximum attenuation levels of 6.8 dB were observed under certain conditions. Huang et al [13] also explored the far-field noise radiation characteristics of ejectors installed on a PDE. The experimental results also showed that ejectors could decrease the peak SPL and the maximum reduction was approximately 8.5 dB.…”
Section: Introductionmentioning
confidence: 99%